The Accidental Trainer: A Reference Manual for the Small, Part-Time, or One-Person Training Department - Miner Nanette (Wiley and Sons, 2006)
When business owners, managers, HRD employees, or experts in their field are responsible for the dissemination of training to their workers, or find themselves thrust into the role of trainer, they are often overwhelmed with the many facets of the task. The Accidental Trainer is a hands-on resource that provides these "accidental" trainers with the basic tools they need to be successful—from understanding the various roles they will play to identifying where best to apply limited time and resources. This book offers a wealth of information for working within the constraints of a small, part-time, or one-person training department. The Accidental Trainer is the "how-to" manual for anyone who needs a trainer's take on how to source, create, or roll out workplace training that hits the mark.